TELEPHYSIOTHERAPY FOR THE TREATMENT OF PHANTOM LIMB PAIN: A QUASI-EXPERIMENTAL STUDY - Luz, Soraia Cristina Tonon da (2024)
Background and objective: Phantom Limb Pain (PLP) is a common complication of extremity amputation, with a prevalence between 41% and 46% of cases. Despite its uncertain pathophysiology, evidence suggests multifactorial mechanisms to explain the painful phenomenon, which directly affects the individual's quality of life. The objective of the study was to analyze the effect of a telephysiotherapy protocol for PLP on the quality of life, intensity and perception of pain in individuals with extremity amputees. Method: Quasi-experimental study with a qualitative-quantitative approach, with a sample consisting of nine individuals. The instruments used were the McGill Pain Questionnaire, the Verbal Pain Scale, the Short-Form Health Survey (SF-36) and an assessment form prepared in an interview format, all applied before and after the treatment protocol. The intervention consisted of an adaptation to the Graduated Motor Imagery (GMI) protocol; held online via the GoogleMeet platform. Quantitative analysis was performed using the paired Wilcoxon test for non-parametric variables and Pearson correlation. The qualitative approach was analyzed using the content analysis method. Results: There was no significant difference in quality of life parameters and pain intensity before and after treatment, but there was a significant decrease in the perception of total pain and emotional components, which was also evidenced in the qualitative reports. Conclusion: The adapted IMG protocol significantly reduced the perception of pain, especially in the emotional aspect, without significant results in the intensity of pain and quality of life of the individual.